Expression of angiogenic proteins in tumor and stroma affects survival in patients with gastric cancer - Nienhüser, Henrik; Crnovrsanin, Nerma; Nerz, Daniel; Heckler, Max; Peters, Leila; Lasitschka, Felix; Schneider, Martin; Schmidt, Thomas (Journal of surgical research, 2020)
Background: Gastric cancer is one of the most frequent malignancies worldwide. Angiogenic growth factors play a crucial role in mediating the crosstalk between cancer cells and the surrounding microenvironment. In this exploratory study, we investigate the impact of angiogenic proteins within the tumor cell or stroma compartment on survival of patients with gastric cancer. Materials and methods: In 29 patients, tumor and stromal compartments were separated using laser capture microdissection. Angiogenic protein expression was measured using a bead-based immunoassay and correlated with tumor stage and overall survival. - Results: Overall survival was signiﬁcantly shorter in patients with a high stroma concentration of vascular endothelial growth factor (VEGF)-A (23.5 (Æ17.6) versus 33.6 (Æ21.0) mo; P ¼ 0.009) and stem cell factor (22.2 (Æ18.5) versus 33.6 (Æ21.8) mo; P ¼ 0.01) compared with patients with a low stroma concentration. High stromal VEGF-D showed a trend toward worse survival (26.8 (Æ22.0) versus 37.2 (Æ19.0) mo; P ¼ 0.09). We did not observe any signiﬁcant correlation between tumor-speciﬁc expression of angiogenic cytokines and survival. - Conclusions: This translational study highlights the difference in clinical impact between tumor and stromal expression of angiogenic proteins. Compartment-speciﬁc concentrations of VEGF-A and stem cell factor affect the clinical prognosis and help to identify the best therapy for patients with gastric cancer.